Vietnam's economic transformation: Embracing change - ZERRILLO, Philip Charles (Institutional Knowledge at Singapore Management University, 2016)
It has been 30 years since Vietnam introduced the ‘Doi Moi’ or economic renovation policy—a commitment to increased liberalisation and structural reforms necessary to modernise the economy. Would you say this has been successful? What are the continuing challenges?